A National Study of Work-Family Balance and Job Satisfaction among Agriculture Teachers - Sorensen, Tyson J.; McKim, Aaron J.; Velez, Jonathan J. (Journal of Agricultural Education, 2016)
This national study sought to extend previous research on the work-family balance (WFB) ability of secondary school agriculture teachers. We utilized data from a simple random sample of agriculture teachers to explore the relationships between work and family characteristics, WFB ability, and job satisfaction. Work role characteristics of interest included weekly work hours, years of teaching experience, and average number of students per class. Family role characteristics included marital status and number of children. Additionally, we considered the influence of other life roles on WFB ability. The number of weekly work hours and being married were significant, negative predictors of WFB ability, while years of teaching experience, average number of students per class, other life roles, and number of children were not statistically significant. In total, work and non-work characteristics accounted for 19% of the variance in the WFB ability of secondary school agriculture teachers. Additionally, teachers in this study reported only moderate levels of WFB ability and job satisfaction. Finally, a significant, positive relationship between WFB ability and job satisfaction was identified. The findings from this research are discussed using the conservation of resources theory, with recommendations and implications highlighted for the agriculture teaching profession.